KESENIAN RODAT DI HULU TERENGGANU - MOHAMED SHAHARUDDIN, SOH AZMY (2016)
This study is a study of Arts Rodat in Hulu Terengganu. The issue in this study is about the least knowledge about this culture. Next, researchers studying the methods of preservation in the right Arts of Rodat. This can be translated through the fact results interviews along the informan expert in this field and is supported distribution of questionnaire. Location is in the vicinity of Hulu Terengganu and Jabatan Kesenian dan Kebudayaan Negeri Terengganu. Overall, this study is unable to achieve the objective through the research problems were analysed by researchers and can be used as a reference to various parties especially students and future researchers.